2014
DOI: 10.3171/2014.7.jns131430
|View full text |Cite
|
Sign up to set email alerts
|

Early reperfusion and clinical outcomes in patients with M2 occlusion: pooled analysis of the PROACT II, IMS, and IMS II studies

Abstract: A solitAry occlusion at the M 2 segment of the middle cerebral artery (MCA) is identified as the cause of stroke in 9%-38% of patients in large thrombolysis series, thus accounting for 16%-41% of all MCA infarctions in this population. [1][2][3]5,8,9,11,13,[15][16][17][18] Unfortunately, the benefit of aggressive intraarterial (IA) intervention for M 2 occlusions remains unclear and the benefit-risk ratio is debatable. Compared with the M 1 segment of the MCA and the internal carotid artery (ICA), M 2 division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…We and others have previously shown that a substantial minority of patients with M2 occlusion have a poor outcome by 3 months (7, 11, 12, 16). Our results show that the anatomical and geometric information of the ASPECTS allows for more specific identification of patients at high risk for poor outcome after isolated M2 occlusion.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We and others have previously shown that a substantial minority of patients with M2 occlusion have a poor outcome by 3 months (7, 11, 12, 16). Our results show that the anatomical and geometric information of the ASPECTS allows for more specific identification of patients at high risk for poor outcome after isolated M2 occlusion.…”
Section: Discussionmentioning
confidence: 86%
“…However, less than 3% of enrolled patients had an isolated M2 occlusion and the majority of patients experience a favorable outcome irrespective of endovascular therapy (4, 7, 11). Hence, identifying imaging parameters that predict poor outcome in this population may aid in the proper patient selection for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A post hoc analysis of the Prolyse in Acute Cerebral Thromboembolism (PROACT) II, Interventional Management of Stroke (IMS), and IMS II studies found successful reperfusion in approximately half of all patients with an M2 occlusion. 10 Shi et al 11 studied 28 patients with an M2 occlusion who were enrolled in the Mechanical Embolus Removal in Cerebral Ischemia (MERCI) and multi-MERCI trials. They found that compared with patients with an M1 occlusion, the number of required passes with the thrombectomy device was lower in those with an M2 occlusion, similar to our data.…”
Section: Discussionmentioning
confidence: 99%
“…M3 segmenti ise insulanın sirkülar sulkusundan başlar ve sylvian fissür yüzeyinde sonlanır (Şekil I) (4,5). Tüm inme nedenleri arasında %9-38 oranında izole MCA M2 oklüzyonu görülür (6). M2 oklüzyonunun akut iskemisinden etkilenen vasküler bölgeler M1 oklüzyonundan daha küçük olsa da M2 oklüzyonu hastalarının %50'sinde mortalite ile veya ciddi sakatlıkla sonlanabilir.…”
Section: Introductionunclassified